2014
DOI: 10.3126/narj.v8i0.11602
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Returns from Improved Rice, Maize and Wheat Research in Nepal

Abstract: Studies on returns to research have been established in different countries to justify research funding and allocation of research priorities. However in Nepal, there are no scientific studies carried out recently on return to research investment in major crops and commodities, despite priority given in agricultural sector. This paper has summarized the research investment with respect to major cereals viz; rice, maize, and wheat and income generated by the impact of improved varieties of these crops in Nepal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The adoption of high yielding improved wheat varieties which are climate suitable and resistant to disease and drought could increase the national production and productivity. Thakur et al (2007) revealed that the adoption of much improved technologies by the farmers have significant effect in rate of change in wheat productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of high yielding improved wheat varieties which are climate suitable and resistant to disease and drought could increase the national production and productivity. Thakur et al (2007) revealed that the adoption of much improved technologies by the farmers have significant effect in rate of change in wheat productivity.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve greater impact of wheat research in Nepal, it is necessary to bridge the gap by making the availability of improved seed with an improved package of practices. Furthermore, Thakur et al (2007) revealed that the adoption of much improved technologies by the farmers have significant effect in rate of change in wheat productivity. Nepal Agricultural Research Council (NARC) was established in 1991 as an autonomous organization under "Nepal Agricultural Research Council Act -1991" to conduct agricultural research in the country to uplift the economic level of the people.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of Haat Bazars are crucial in promoting sustainable economic development and empowering rural communities in Nepal (Ghimire, 2017).Haat Bazars, also known as weekly or biweekly markets, are a ubiquitous feature in rural areas of Nepal, including the Rupandehi district (Makar, 2019). These markets play a pivotal role in the economic growth of Nepal by providing a platform for small and marginal farmers to sell their produce directly to consumers on specific market days (Ghimire, 2017).…”
Section: Introductionmentioning
confidence: 99%